Critical Issues in Teacher Leadership: A National Look at Teachers' Perception. Issue 3 (May 2016) - Jacobs, Jennifer; Gordon, Stephen P.; Solis, Rachel
The purpose of this qualitative study was to identify (1) teacher-leaders' descriptions of their roles and activities, (2) perceptions of characteristics, knowledge, and skills of successful teacher leaders, (3) barriers to and support needed for teacher leadership, (4) the extent to which teacher leaders helped teachers understand and respond to different cultures, and (5) the rewards of teacher leadership. Phase I of the study consisted of a survey of 177 teacher leaders across eight states representing all regions of the country. In Phase II we conducted interviews with 20 of the survey respondents to supplement survey data. Findings point to the complex nature of the roles and activities of teacher leaders. The data have implications for teacher leadership preparation and the ongoing support teacher leaders will need to actualize their roles within schools.